Engineering for Rural Development 2019
DOI: 10.22616/erdev2019.18.n447
|View full text |Cite
|
Sign up to set email alerts
|

Methodological aspects of training future agroengineers

Abstract: The purpose of this study is to reveal the methodological aspects of teaching the disciplines that are basic in the system of training an engineer for modern agricultural production, in particular during the lecture sessions. The paper presents the basic requirements for the modern teacher who teaches special disciplines, training an engineer in the field of agricultural mechanisation. Emphasis is placed on theoretical aspects, as well on the results of the acquisition and generalisation of practical experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Table 2 Distribution of the students from the experimental and the reference groups by the levels of their educational and cognitive activity (K (1) By the way, the educational achievements of these students, who were registered according to the results of the current and the final controls (the exam on the course, defence of the course paper), were significantly higher compared to the results of students in the reference massif. At the exam most students freely operated with the necessary technical terms, thoroughly possessed the skills of calculating parts, units, gears.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 Distribution of the students from the experimental and the reference groups by the levels of their educational and cognitive activity (K (1) By the way, the educational achievements of these students, who were registered according to the results of the current and the final controls (the exam on the course, defence of the course paper), were significantly higher compared to the results of students in the reference massif. At the exam most students freely operated with the necessary technical terms, thoroughly possessed the skills of calculating parts, units, gears.…”
Section: Resultsmentioning
confidence: 99%
“…He is ready to persistently seek and find new productive knowledge in other areas as well. That is, in addition to the narrow specialised knowledge, a professional also has a deliberate, normal need (hence -motivation → motive) to learn new things independently and constantly [1]. The conducted analysis revealed a contradiction between the need to raise the level of the students' cognitive independence and the limited possibilities to use the available didactic tools that do not fully take into account the selection of the content, methods and pedagogical abilities to control the students' educational achievements [2].…”
Section: Introductionmentioning
confidence: 99%
“…The review aimed to summarize the current level of research focused on education and curricula, touching on the concept of competencies and covering a period of 20 yearsfrom 1997 to 2017. Based on this review, the authors suggested that there are two different labels for "competencies" in education [2]. Namely: from the theoretical point of view, competence is conceived as a cognitive structure that promotes a certain behavior; from the operational point of view, competencies, the authors suggest, cover a wide range of higher-order skills and behaviors, representing the ability to deal with complex, unpredictable situations; this operational definition includes knowledge, skills and strategic thinking, and assumes conscious and intentional decision-making [3].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the task of creating conditions that ensure continuous development of the professional potential of the student's personality comes to the foreground. In psychological and pedagogical scientific works, there are increasingly studied problems, associated with the need to increase the level of cognitive independence of the students, which as a result, are transformed into a readiness for professional activity and professional self-improvement [1]. The quality level of training of the future engineers not fully meets the needs of modern production and directly depends on their interest and participation in the practical and research work in their chosen specialty [2].…”
Section: Introductionmentioning
confidence: 99%